Morphological Error Analysis: a Review of the Aspects of Imla and Insya Errors in Writing Arabic Sentence Structures at Muhammadiyah 5 Tangerang Middle School - Azzahra, Natasya; Fahmi, Ari Khairurrijal (Jurusan Pendidikan Bahasa Arab, 2026)
This study aims to describe the forms of morphological errors in writing insyā’ in kitābah learning at Muhammadiyah Junior High School and calculate the percentage of their occurrence using the Error Analysis approach. The study used a descriptive qualitative method with data collection techniques in the form of documentation of students' writing results and interviews with subject teachers. The analysis process was carried out through four stages of error analysis, including: error identification, error classification, explanation of the source of errors, and calculation of the frequency and percentage of errors. The results showed that there were two dominant types of errors, namely harakat errors and letter writing errors, each accounting for 5 errors out of a total of 10 errors found. The percentage of errors showed that harakat errors reached 50%, while letter writing errors also reached 50%. These findings indicate that students' ability to apply the basic rules of Arabic morphology and orthography is still low, especially in terms of the accuracy of vocalization and letter formation. This study recommends strengthening error analysis-based exercises and structured remedial learning to improve students' insyā' skills.